Access to Credit, Human Resource Development, Market Orientation, and Regulatory Compliance: Determinants of MSME Sustainability in Indonesia - Hery Purnomo; Subagyo Subagyo; Faisol Faisol; Dodi Kusuma Hadi Soejoko; Poniran Yudho Leksono (West Science Social and Humanities Studies, 2024)
In this study, structural equation modeling (SEM) is used to conduct a quantitative analysis aimed at determining the factors that influence the sustainability of micro, small, and medium-sized enterprises (MSMEs) in Indonesia. The four main themes of the study are market orientation, regulatory compliance, human resource development, and credit availability. Following a survey of 200 MSMEs, the collected data underwent thorough statistical analysis. The findings show a strong positive correlation between regulatory compliance and MSME sustainability, human resource development, and loan availability. Although it had a beneficial effect, market orientation fell short of statistical significance in this investigation. The study adds to our knowledge of the intricate processes affecting MSMEs' sustainability in the Indonesian environment and provides insightful information to scholars, policymakers, and entrepreneurs.